Case report and literature review: Laparoscopic extended right hemicolectomy for a 55-year-old patient with idiopathic mesenteric phlebosclerosis - Liu, Siyu; Tong, Yujun; Shi, Ruizi; Zeng, Xintao; Luo, Hua; Yang, Pei; Cai, Xianfu; Wang, Decai; Luo, Huiwen; Wang, Jianjun (Frontiers in Medicine, 2024)
Idiopathic mesenteric phlebosclerosis (IMP) is an extremely rare disease with an unclear pathogenesis and risk factors. The clinical manifestations of IMP are mostly non-specific, mainly consisting of digestive symptoms such as abdominal pain, bloating and diarrhea. The diagnosis of IMP mainly relies on abdominal computed tomography (CT) and colonoscopy. Pathological changes associated with IMP often involve fibrous degeneration of the venous wall, which results in the thickening of the colonic wall and longitudinal calcification of the mesenteric arteries. Currently, there is no standard treatment protocol for IMP, and nonsurgical treatment is the mainstay of most medical centers. In this study, we reported a case of a 55-year-old female patient with IMP whose main clinical presentation was recurrent abdominal pain. The patient’s initial diagnosis was considered an incomplete intestinal obstruction and received non-surgical treatments; however, the efficacy of the treatment was unsatisfactory. After completing abdominal CT and colonoscopy, we excluded common diseases of the digestive system (e.g., tumors, Crohn’s disease), and finally considered that this patient had a high likelihood of IMP. This patient eventually underwent laparoscopic enlarged right hemicolectomy due to recurrent symptoms and poor outcomes of non-surgical treatment. Postoperative pathological results confirmed the diagnosis of IMP. During the follow-up period, the patient recovered well without recurrence of IMP. Furthermore, we have reviewed the literature related to IMP and summarized the etiology, risk factors, diagnostic methods, treatment options and prognosis of IMP.